Improved Correlator Peak Selection for GNSS Receivers in Urban Canyons. (September 2015) - Xie, Peng; Petovello, Mark G.
<x content-type="archive" xml:space="preserve">Abstract</x> Multipath arises from the reception of reflected or diffracted signals in addition to the Line-Of-Sight (LOS) signal. By using a block processing high sensitivity receiver scheme, this paper aims to obtain better positioning performance in urban canyon areas. Generally, the peak with the most power is utilised in high sensitivity receivers; however, this approach is not always optimal in multipath environments. Noting that signal correlation peaks may be separated in the Doppler domain by a long coherent integration time, a peak identification scheme is proposed in this work, which yields better positioning performance. It is shown that most of the multipath peaks are removed in the receiver after using the proposed algorithm.